PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PELANGGAN ES KRIM AICE DI KOTA DEPOK - Yuaniko Paramitra (Jurnal Ekonomi dan Industri, 2023)
The purpose of this study was to analyze the mediating effect of product quality, price and purchase decision on AICE ice cream consumers in Depok City. Respondents in this study were the consumers of AICE ice cream in Depok City, the analytical method used was regression. The results of the study stated that the influence of product quality and price on Purchase Decision simultaneously have a significant influence. the influence of product quality on purchase decision partially have a significant influence and the influence of price on purchase decision also have a significant influence.